SOSIALISASI DAN IMPLEMENTASI APRESIASI DALAM PERENCANAAN ANGGARAN DAN REALISASI DI RS ISLAM JAKARTA SUKAPURA, JAKARTA UTARA - Nur Asni Gani; Jaharuddin Jaharuddin; Teguh Pantjatmono; Andry Priharta; Rony Edward Utama; Tri Ananto (Media Resonansi Pengabdian Masyarakat, 2025)
This community engagement program aims to support the implementation of the Budget Planning and Realization Application (APRESIASI) at RSIJ Sukapura, North Jakarta, as a strategic step to enhance transparency, efficiency, and accountability in hospital budget management. The program was conducted in two phases, on October 22, 2024, and January 24, 2025, at the Auditorium of the Muhammadiyah Da'wah Building, Muhammadiyah Regional Leadership (PDM) North Jakarta, utilizing lectures by expert speakers followed by interactive discussions with participants. The implementation stages included preparation, socialization, technical assistance, and evaluation and follow-up. The socialization phase aimed to provide a comprehensive understanding of the application's features and benefits, while the technical assistance phase focused on operational aspects such as budget planning, approval processes, and budget realization. The results indicate that a portion of the hospital’s budget data has been successfully inputted into the system, providing an initial overview of digital budget implementation, although further data refinement and user capacity building are still required. The discussions also yielded valuable insights, including the need for budget flexibility to accommodate unplanned activities and the importance of regular evaluations to align with the hospital’s operational needs. Recommendations include enhancing user capacity through continuous training, optimizing application features, and strengthening coordination among hospital units to ensure effective system utilization. This program is expected to facilitate the optimal implementation of the APRESIASI application, supporting more accurate and accountable budget management, and contributing to the advancement of digital financial systems in hospitals.Keywords: Budget management, digitalization, hospital, APRESIASI, community engagement.